2013
DOI: 10.1111/nmo.12197
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment with otilonium bromide induces changes in L‐type Ca2+channel, tachykinins, and nitric oxide synthase expression in rat colon muscle coat

Abstract: Chronic exposition to OB significantly affects the NKr/SP/NO circuit. The progressive decrease in SP-expression might be the consequence of the persistent presence of OB, the increase of NOS1 expression in muscle cells at 10 days in an attempt to guarantee an adequate NO production, and, at 30 days, the redistribution of the L-type Ca²⁺ channel and NK1r as a sign to compensate the drug channel block by re-cycling both of them. The physiological data suggest NK1r hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…It has been reported that low levels of NO represent a stimulus for constitutive NOS transcription and synthesis [16], [18] and that the SMC respond to similar stimuli very rapidly [19]. In this regard, we previously demonstrated that chronic OB exposure induced a significant increase in the muscular nNOS at 10 days [12]. Therefore, this early increase in eNOS might represent the attempt by the SMC to counteract the decrease in intracellular calcium availability due to the OB block of calcium entry [11], [20], [21].…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…It has been reported that low levels of NO represent a stimulus for constitutive NOS transcription and synthesis [16], [18] and that the SMC respond to similar stimuli very rapidly [19]. In this regard, we previously demonstrated that chronic OB exposure induced a significant increase in the muscular nNOS at 10 days [12]. Therefore, this early increase in eNOS might represent the attempt by the SMC to counteract the decrease in intracellular calcium availability due to the OB block of calcium entry [11], [20], [21].…”
Section: Discussionmentioning
confidence: 57%
“…A possible explanation for these results likely relies on the absence of L-type Ca 2+ channels and Mr2 in the ICC. The findings that the amplitude and frequency of slow waves [13] and the spontaneous motility [12] were not modified by OB treatment further underlie the ICC are not involved in the drug action.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations